The Roles of Performance Measures and Monitoring in Annual Governance Decisions in Entrepreneurial Firms - Engel, Ellen; Gordon, Elizabeth A.; Hayes, Rachel M. (Journal of Accounting Research, 2002)
This paper analyzes annual corporate governance decisions at firms making initial public offerings (IPOs) of common stock between 1996 and 1999. Our objective is to examine relations between firms’ corporate governance decisions and the informativeness of available measures of managerial performance. We consider financial measures such as earnings and stock return, as well as direct monitoring. We collect a sample of IPO firms from the manufacturing, Internet, and technology (non‐Internet) industries, and examine how the use of various performance measures in annual compensation grants and turnover decisions varies with the information environment of the firm and with the extent of venture capital influence. Consistent with prior research that finds earnings are of limited usefulness in firm valuation for Internet firms, we find Internet firms place less importance on earnings and greater importance on stock returns in determining compensation grants than do non‐Internet firms. We also find that compensation grants of firms with little or no venture capital influence display significantly stronger association with accounting and stock performance measures than those of firms with more intense monitoring by venture capitalists. This result is consistent with direct monitoring and the use of explicit performance measures acting as substitute governance mechanisms.